Ekologi Media Radio Siaran di Yogyakarta: Kajian Teori Niche terhadap Program Acara Radio Siaran di Propinsi Daerah Istimewa Yogyakarta - Herawati, F. Anita; Budi HH, Setio (Jurnal Ilmu Komunikasi, 2007)
Abstract: This article describes the radio competition in Yogyakarta at 2005. The radio competition was measured by using niche theory and as an unit of analysis is radio program. Niche theory was applied by measuring niche breadth and niche overlap. Niche breadth shows the degree of radio competition which focuses on the source of media life. Another measurement is niche overlap. This concept is used to measure what radio becomes competitor to certain radio. This research shows that the radio industries in Yogyakarta tend to be specialist radio and the radio competition is very strong.